Investigation on Shear Capacity of Joints between Steel Reinforced Concrete Special-Shaped Column and Reinforced Concrete Beam - Xiang, Ping; Lin, Yipeng; Huang, Wei; Ding, Faxing; Ye, Bailong; Deng, Zhiheng (Frontiers in Materials, 2020)
Steel reinforced concrete special-shaped column structural has all priorities of steel reinforced structure and special-shaped column structure. The design of steel reinforced concrete special-shaped column joints is of great importance to ensure that this new structural can be widely used in earthquake area. This research adopted the new joint design style, and the pseudo-static test is carried out on three joints (JD-1, JD-2 and JD-3) between the steel reinforced concrete special-shaped column and the reinforced concrete beam, and one joint (JD-4) between reinforced concrete special-shaped column and concrete beam. The working mechanism of joints and the function of steel in the shearing-resistant mechanism are analyzed. Based on the results of experimental research, this article put forward formulas on the cracking capacity and shearing resistant capacity of these joints with theoretical and applicative purposes. Take into account all these facts, the behavior of high resistant capacity and reliability of the joint design method has been manifested. Some conclusions derived from this research can be used as a reference for engineering practice.